Antibacterial Effect of Dentin Bonding Agents: (An in vitro Study) - Mahmoud Y Taha; Nadia M Al-Shakir; Nawal A Al-Sabawi (University of Mosul, College of Dentistry, 2013)
Aims: To evaluate and compare the antibacterial effect of three types of dentin bonding agents. Also, to evaluate the antibacterial effect after different time intervals (24, 48, and 72) hs. Materials and Methods: Materials tested in this study were G bond, Single bond (SB), and Excite bond. Tested mi-croorganisms were Enterococcus faecalis (E. faecalis) and Streptococcus mutans (S. mutans). The antibacterial activity were investigated by agar diffusion test performed with adhesives cured on the surface of dentin discs. Also, the antibacterial effect were investigated by evaluation of growth inhibi-tion after 24, 48, and 72 hrs microplate direct contact test using spectrophotometer. The data were ana-lyzed statistically using one way ANOVA and Tukeyʼs test. Results: G bond had antibacterial effect by the two tests and against the two examined bacteria significantly higher than SB and Excite, also SB significantly had antibacterial effect better than Excite bond. The result also revealed that antibac-terial effect of SB and Excite Bond significantly decreased by the time while G bond was not signifi-cantly decrease. Conclusions: Under the limitation of the present study, it is concluded that G bond is able to delay bacterial growth during restorative treatment of dental caries